2016
DOI: 10.1371/journal.pone.0168915
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Structural Analysis of a Highly-Expressed Yersinia pestis Small RNA following Infection of Cultured Macrophages

Abstract: Non-coding small RNAs (sRNAs) are found in practically all bacterial genomes and play important roles in regulating gene expression to impact bacterial metabolism, growth, and virulence. We performed transcriptomics analysis to identify sRNAs that are differentially expressed in Yersinia pestis that invaded the human macrophage cell line THP-1, compared to pathogens that remained extracellular in the presence of host. Using ultra high-throughput sequencing, we identified 37 novel and 143 previously known sRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…Similar findings were obtained in a yersiniosis mouse model infected with Y. pseudotuberculosis and in which multiple sRNAs were mutated [85]. More than 180 sRNAs, including 37 new ones, were discovered upon deep RNA-seq of the Y. pestis transcriptome and sequence analysis of sRNA candidates [84]. A more prominent role for sRNAs in virulence is to be expected.…”
Section: Gram-negative Bacteriasupporting
confidence: 72%
See 1 more Smart Citation
“…Similar findings were obtained in a yersiniosis mouse model infected with Y. pseudotuberculosis and in which multiple sRNAs were mutated [85]. More than 180 sRNAs, including 37 new ones, were discovered upon deep RNA-seq of the Y. pestis transcriptome and sequence analysis of sRNA candidates [84]. A more prominent role for sRNAs in virulence is to be expected.…”
Section: Gram-negative Bacteriasupporting
confidence: 72%
“…In bacterial species, such as Yersinia pestis (the infectious agent of bubonic plague), the T3SS is a significant virulence factor that is required to deliver mostly bacterial protein effectors to the host [83]. Functional studies on YsR40 sRNA (362 nt in length) have shown that its knock-down reduces infection efficiency in host cell culture and bacterial cell growth in response to stress [84]. Similar findings were obtained in a yersiniosis mouse model infected with Y. pseudotuberculosis and in which multiple sRNAs were mutated [85].…”
Section: Gram-negative Bacteriamentioning
confidence: 99%
“…Most sRNAs post‐transcriptionally upregulate or downregulate downstream gene expression by affecting the stability and translational efficiency of target messenger RNAs (mRNAs) through base pairing with them 12,13 . A wide variety of physiological processes, including metabolism, stress responses, and the expression of virulence genes, are regulated by sRNAs 14–18 . In B. pertussis , many types of sRNAs have been identified or predicted by an in silico analysis and RNA‐seq on the bacteria grown in vitro 9,11,14 .…”
Section: Srna Coordinatea Predicted Srna Size (Base) Igr Lengthb Adjamentioning
confidence: 99%
“…Recent work has also identified multiple sRNAs of Y. pestis , which are upregulated within macrophages. Among them is Ysr170, which was shown to be important for intracellular replication (Li et al, 2016 ). Much more is known about conserved sRNAs and their impact on pathogenicity of Yersinia .…”
Section: Control By Regulatory Rnasmentioning
confidence: 99%